The effects of judicialization on the budget of the Municipal Health Department of Canguçu/RS - Manetti da Cruz, Cristiano; Pandolfo Provin, Mercia; de Sene Amâncio Zara, Ana Laura (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: To identify expenses with the purchase of medicines and supplies by the Municipal Health Department of Canguçu/RS, through legal proceedings, from 2017 to 2021. Methods: It is a quantitative, descriptive, and retrospective study, using the docu-ment analysis technique. Secondary data on public costs, available on the Transparency Portal, were used. The amounts spent and the origins of the resources used for the acqui-sition of these drugs were analyzed. Results: There was an increase of 297.93% in spen-ding on legal proceedings for the acquisition of medicines and pharmaceutical supplies through judicial blockades. Of these, more than 76% refer to antineoplastic medications. The basic care budget increased by 132.41% in this period and the costs of pharmaceu-tical assistance almost doubled from R$ 854,248.86, in 2017, to R$ 1,524,871.92, in 2021, with a significant increase during the pandemic period. Comparing the expen-diture on purchasing medicines through blockages by court permits in 2021 and the amount spent on pharmaceutical assistance in the same period, it is noted that the cost is very similar, but a small portion of the population is served through judicialization. Conclusions: There was a considerable increase in spending on purchasing medicines due to court decisions. The Municipal Health Department is obliged to acquire medicines that do not belong to the Municipal Medication List, through judicial blocking of public accounts, because the government of the State of Rio Grande do Sul does not send these medicines to users with approved lawsuits.